Estudo da síntese in situ de nanopartículas e filmes finos de óxido de zinco dopado com alumínio por rota hidrotermal convencional e assistida por micro-ondas - Serrão, Fernanda Thamiles de Jesus (2023)
Zinc oxide (ZnO) is one of the most interesting materials due to its wide range of applications in various optoelectronic devices, such as light-emitting diodes, photodetectors, sensors, UV absorbers, solar cells, among others. However, ZnO's low electrical conductivity limits several of its applications, despite being a promising material for optoelectronic devices due to confinement effects. One way to overcome this problem is by doping, substituting Zn2+ ions with group III ions (B3+, Al3+, Ga3+, and In3+), which can promote electrons to the conduction band and improve the optical, thermal, magnetic, and electrical properties of ZnO. Among these dopants, Al3+ is the most commonly used due to its small ionic radius and low production cost. In this context, this study aims to synthesize and analyze the synthesis parameters of Al-doped ZnO nanoparticles (AZO) by using hydrothermal routes under conventional heating and assisted by microwave irradiation, in an aqueous medium. The materials and synthesis parameters will be characterized using X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, transmission electron microscopy (TEM). For the syntheses deposited on glass substrates, optical microscopy (OM) and scanning electron microscopy (SEM) were performed.